PENGARUH COMPACTION RATIO TERHADAP SIFAT PAPAN LANTAI PARTIKEL KAYU JATI DAN SENGON - Widayanto, Widayanto; Morisco, Morisco; Prayitno, T.A. (Civil Engineering Forum Teknik Sipil, 2007)
Wood particle board is one of building materials which can be used as floor like solid wood. To utilize particle boards with appropriate compaction ratio, study should be conducted to know the influence of compaction ratio on the particle board characteristics of two wood species namely teak and sengon, and the research result could be used as a base of the assessment to particle board for building. The preliminary test was done to know the density of teak and sengon wood. This study used teak and sengon wood particles with 10% by weight of particle urea formaldehyde adhesive UA-147. This study was arranged in the completely randomised design with factorial experiment. The factors in this experiment were compaction ratio and wood species, while the parameters which observed were density, water content, water absorption, thickness swelling, internal bonding, hardness, MOE, and MOR. The research result showed that the higher compaction ratio, the higher density, internal bonding, hardness, MOR and MOE of both species particle board, the higher thickness swelling, and the lower water absorption of sengon particle board. The highest average density of the teak particle board was 0,80 g/cm3 (J1K3) and 0,67 g/cm3 for sengon (J2K6). The highest average internal bonding of the teak particle board was 5,20 kg/cm2 (J1K3) and 5,85 kg/cm2 for sengon (J2K6). The highest average hardness of the teak particle board was 666,7 kg/cm2 (J1K3) and 533,3 kg/cm2 for sengon (J2K6). The highest average MOR of the teak particle board was 145,9 kg/cm2 (J1K3) and 162,7 kg/cm2 for sengon (J2K6). The highest average thickness swelling of the sengon particle board was 30,76% (J2K4) and 11,84% the lowest (J2K3). The highest average MOE of the sengon particle board was 18605,45 kg/cm2 (J2K6) and 22580,41 kg/cm2 for the teak (J1K3). The highest average water absorption of the sengon particle board was 170,30% (J2K1) and 72,12% the lowest (J2K6). With the same compaction ratio of the teak and sengon particle board, the teak wood species had the better physic and mechanic characteristics than sengon. Based on the comparation result with some industries standard of the particle board, it showed that particle boards J2K1, J2K2, and J2K3 did not correspond to some industries standard.